Eyewitness Memory: Attention as a mechanism for enhanced suggestibility - Hodhod, Taylor S. (Tufts Archival Research Center, 2017)
In standard eyewitness misinformation paradigms, research has revealed that taking a memory test on an originally encoded event prior to the presentation of post-event information enhances learning of subsequent misleading details. That is, participants are more likely to incorrectly report suggested details if they had taken a test on the original event than if they had not taken a test. Further, research suggests that prior testing may influence attention and encoding processes directed towards post-test material. The present study examined whether increased suggestibility is dependent on testing. Misinformation susceptibility was compared across conditions in which attention to the post-event information was manipulated. Toward this end, attention was manipulated through a secondary visual task: during the presentation of the audio narrative, participants were prompted to make a keyboard response when presented with a visual probe. The present study sought to determine whether changes in attention are dependent on the temporal proximity of the probe to critical narrative details. Results highlight the importance of the temporal proximity between the visual probes and critical details during narrative presentation. Consistent with previous research, results suggest that manipulations intended to draw attention to inconsistencies within a misleading post-event narrative may serve to enhance suggestibility.